Crises Management Strategies of Private Secondary School Principals in Port Harcourt Local Government Area, Rivers State, Nigeria - Innocent Nnochiri; ROBERT-OKAH, I (Zien Journals, 2022)
The study investigated principals’ crisis management strategies for enhancing secondary school crises management of private secondary schools in Rivers State. Five research questions guided the study; the study adopted descriptive survey research design. The population of the study comprised 293 principals randomly selected from the private secondary schools in Rivers State. Simple random sampling techniques were used to select 293 respondents (representing 100% in the population) for the study. The researchers’ developed structured questionnaire was the instrument used for data collection titled “Crisis Management Strategies Scale of Principals (CMSSP)”. The instrument was validated by two experts in Educational Management. The questionnaire was face validated by experts in the field of education, reliability coefficient of 0.65 was obtained using Croanbach Alpha method of determining internal consistency of the instrument using the Statistical Package for the Social Science (SPSS). Mean and standard deviation were used to answer the research questions while the z-test was used to test the null hypotheses at 0.05 Alpha level of significance. The study revealed that the private principals’ communication, third party decision making, joint problem solving strategies and containment control strategies can help in resolving crises in schools. However, the contrary as revealed by the study is confrontation strategy which if applied will trigger crises in schools in Rivers State. Based on the findings of the study, it was recommended among others that the district Education office should organize seminars and workshops aimed at improving rapport between principal and their staff/students, effective communication on long and short term negative effects of crisis should be made between teachers, principals and parents, the guidance and counseling should be strengthened to educate both principal and teacher on better strategies of managing crisis in secondary schools.
Keywords: Crisis; Education; Management; Private